A Clarity Model of District Representation: District Magnitude and Pork Priorities. Issue 1 (2nd December 2020) - Tromborg, Mathias Wessel; Schwindt‐Bayer, Leslie A.
Abstract : Carey and Shugart's important personal vote seeking model has long dominated literature on electoral rules and district representation. Empirical support for the model is somewhat mixed, however. We think one reason may be that its applicability depends on the type of district‐focused representation. We present an alternative "clarity model, " drawing from Lancaster, that may work better for one specific type of district‐targeted representation—pork provision. The clarity model posits district magnitude should be linked to less pork regardless of ballot type because it limits clarity of responsibility for pork outcomes. Legislators not directly responsible for goods and services allocated to the district can still claim credit for them in high magnitude districts. We test this theory with elite survey data on legislators' priorities toward pork provision in 14 Latin American and 10 Western Europe democracies and find empirical support for a clarity theory of pork priorities.